Situation report on Nepal’s agrifood systems : April 2023 - Kishore, Avinash; Saroj, Sunil; Minot, Nicholas; Dorosh, Paul A.; Parajuli, R.R.; Krupnik, Timothy J. (CSISA, 2023)
Nepal’s agrifood system remained economically stable during March of 2023. The year-on-year inflation in food and beverage prices has cooled down to 5.6% compared to 7.5% in Feb/March 2022. Field reports however suggest that this downward movement in prices have not yet translated to substantial changes in the cost of consumer and agricultural market goods. Inflation in food and beverage prices is marginally lower than the previous year: The cost of food and beverages increased by 5.6 percent from March 2022 to March 2023. A sharp 8.8 percent decline in the price of vegetables compared to last year helped lower the inflation in food prices. Food inflation was the highest in the mid-hills and mountains (8.8 percent) and the lowest in the Kathmandu Valley (4.5 percent). Cereal prices remain high even after decent harvests of paddy, maize, and wheat: Annual inflation in the price of cereals and cereal-based processed foods increased from 9.6 percent in January 2023 and 12.4 percent in February 2023 to 14.4 percent in March despite a small increase in the domestic production of paddy and negligible changes in the projected outputs of wheat and maize compared to the last year. The continuing embargo on the export of broken rice and quotas and on wheat exports by India is partly responsible for the persistently high prices of cereals in Nepal. Agricultural laborers experienced a decline in their real wages: Wage rates of agricultural laborers increased by 4.7 percent over the 12 months leading up to March 2023, less than the 7.4 percent increase in the overall consumer price index (CPI) and the 5.6 percent increase in food prices. In effect, real wages of agricultural laborers in rural areas have declined. In many areas, the poorest Nepali families may depend on agricultural labor and spend a larger share of their household budget on cereals and cereal products whose prices have increased by 9-14 percent over the past 12 months. The recent rise in consumer prices—the highest since 2016-17— will have the largest negative effect on these households. Stable production despite fertilizer shortages: Favorable weather conditions and the availability of quality seeds allowed farmers to increase production of paddy and maintain wheat and maize production despite inconsistent chemical fertilizers. Reductions in fertilizer subsidies: In March of 2023, the Government of Nepal announced a reduction in nitrogen, phosphorous, and potassium fertilizer subsidies alongside a large increase in import of fertilizers from abroad. While farmers already tend to pay higher than subsidized prices for farmers, the dramatic reduction in subsidies could increase prices and potentially introduce further instability in fertilizer markets in the short term. This is anticipated to hurt cash-strapped smallholder farmers the most, with potential negative implications for agrovets who may have insufficiently stocked fertilizers for sale prior to the decreases in subsidy.